2021
DOI: 10.3389/fsurg.2021.701207
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Three-Dimensional Reconstruction in Percutaneous Nephrolithotomy for Complex Renal Calculi Treatment

Abstract: Introduction: Three-dimensional (3D) reconstruction is a novel imaging technique widely used to improve surgical operations. Some studies have identified its role in Urology for percutaneous nephrolithotomy (PCNL).Objective: To explore the potential benefits of 3D reconstruction technology in PCNL for complex renal calculi treatment.Methods: A retrospective study involving 139 patients with complex kidney stones who underwent PCNL was conducted between September 30, 2018, to September 30, 2019. Group A patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…There were insignificant differences in operation time, hemoglobin drop, or complication rates between groups. Both studies concluded that 3D reconstruction technology is an effective adjunct to PCNL in complex renal calculi treatment, recommending the Hisense CAS System to assist in preoperative planning and intraoperative navigation for an intuitive, precise, and convenient PCNL [17,18].…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were insignificant differences in operation time, hemoglobin drop, or complication rates between groups. Both studies concluded that 3D reconstruction technology is an effective adjunct to PCNL in complex renal calculi treatment, recommending the Hisense CAS System to assist in preoperative planning and intraoperative navigation for an intuitive, precise, and convenient PCNL [17,18].…”
Section: Key Pointsmentioning
confidence: 99%
“…A retrospective study of 139 patients with complex kidney stones submitted to PCNL investigated the results of 3D reconstruction using a computer-assisted surgery system (CAS; Hisense Technology, Qingtao, CN) vs. plain CT preop planning [17]. Patients were grouped into those submitted to the 3D reconstruction technique before PCNL ( n = 72) and those not ( n = 67).…”
Section: D Imaging For Pre-operative Planningmentioning
confidence: 99%
“…In particular, three-dimensional computed tomography (3D-CT) reconstructions have been adopted to facilitate comprehensive planning for PCNL ( 31 , 32 ). In 2021, Tan et al ( 32 ) published a retrospective comparative study including 139 patients with complex renal calculi undergoing PCNL. In 72 cases the procedure was preceded by 3D-CT reconstruction techniques.…”
Section: Three-dimensional Reconstruction Technologiesmentioning
confidence: 99%